The comparison of the effect of variable and constant resistance training on the salivary testosterone, cortisol and growth hormone in trained men - Alireza Emtiaz; Seyed Alireza Hosseini Kakhk; Amir Hossein Haghighi (Shahid Beheshti University, 2023)
Background and Purpose:  Variable resistance training (VRT) is a type of resistance training that helps to improve muscle strength and function through extra resistance such as elastic bands and chains. The comparison of the effect of constant resistance training (CRT) versus VRT on hormonal response has not been fully studied. So, this study investigated the acute and chronic effects of VRT versus CRT on the salivary concentration of testosterone, growth hormone, and cortisol in trained men.Material and Methods: 30 young resistance-trained men were recruited for this study and were randomly assigned to three groups including VRT, CRT, and control. Both training groups performed an exercise protocol with an intensity of 65 to 85% of 1RM for 10 weeks and 3 sets (three sessions per week). The training included the main upper and lower extremity exercises and the rest period between the sets and exercises was 1 and 2-3 minutes respectively.In addition, the VRT  group used 7.5 kg chains as an external variable resistance. Oral saliva samples were collected before and after the first session (acute response) and the last session (chronic response) and then analyzed by ELISA method. Inter-group changes were analyzed by repeated measures analysis of variance and Bonferroni's post hoc test. The significance level was also considered equal to P £ 0.05.Results: a significant group×time interaction was observed only for the acute response of salivary testosterone (P = 0.003). So, a significant increase was observed in the salivary of testosterone in the VRT compared to CRT (P = 0.001) and control (P = 0.003), although no significant differences were observed for cortisol (P=0.64), growth hormone (P = 0.52)  and testosterone to growth hormone (P = 0.49). Also, no significant group×time interaction was observed for testosterone (P = 0.377), cortisol (P=0.57), testosterone to cortisol ratio (P = 0.91), and growth hormone (P = 0.200) in chronic response (P > 0.05).Conclusion: The results showed that a session of VRT caused a significant increase in testosterone hormone immediately after exercise, but 10 weeks of VRT or CRT had no significant effect on the levels of testosterone, cortisol, and growth. It seems that if VRT is performed with higher intensity or volume, additional hormonal responses will occur as a result of exercise, and therefore the effectiveness of the exercise will promote.